Teachers discovering computers : integrating technology in a connected world - Shelly, Gary B.; Gunter, Glenda A.; Gunter, Randolph E. (Shelly Cashman series, 2012)
Teachers Discovering Computers: Teaching in a Connected World, Seventh Edition introduces future educators to technology and digital media in order to help them successfully teach the current generation of digital students